Synthesis and characterization of copper complexes with tripodal ligands bearing amino acid groups. Issue 8 (8th March 2021) - Gawlig, Christopher; Jung, Jannis; Mollenhauer, Doreen; Schindler, Siegfried
Abstract: The tripodal ligand (2‐aminoethyl) bis (2‐pyridylmethyl)amine (uns‐penp), known for its Cu/O2 intermediates, was modified at one side arm by a selection of amino acids. With L‐Tyrosine (Tyr), L‐Histidine (His) and L‐Lysine (Lys) it was possible to introduce chirality into the tripodal ligand system and to investigate the corresponding copper(I) complexes [Cu{L‐His(BPh3 )uns‐penp}], [Cu(L‐Lys)uns‐penp]OTf and [Cu(L‐Tyr)uns‐penp]OTf. [Cu{L‐His(BPh3 )uns‐penp}] could be structurally characterized and represents the first example of a copper(I) complex with a coordinated imidazole ring of the histidine ligand. Furthermore, these complexes demonstrated catalytic activity for the oxygenation of thioanisole with hydrogen peroxide as an oxidant. Abstract :